The intensity and timing of investment: The case of land - Li, Yuming; Capozza, Dennis R. (American Economic Review, 1994)
The authors model the decision to replace durable capital when intensity is variable. Decisions of this type include land-redevelopment decisions where the density of residential or commercial development is a choice variable as well as capital-replacement decisions where capacity is variable. The authors provide a general yet simple formation of the problem using an optimal-stopping framework. They characterize the value of the project, the timing of investment, and the intensity of development. The authors show that intensity interacts in important ways with timing, taxes, and project values. The ability to vary intensity raises hurdle rents and delays development decisions. Copyright 1994 by American Economic Association.